Polymer Nanomedicines with Ph-Sensitive Release of Dexamethasone for the Localized Treatment of Inflammation - Alena Libánská; Eva Randárová; Franck Lager; Gilles Renault; Daniel Scherman; Tomáš Etrych (MDPI AG, 2020)
Polymer-drug conjugates have several advantages in controlled drug delivery to inflammation as they can accumulate and release the drug in inflamed tissues or cells, which could circumvent the shortcomings of current therapy. To improve the therapeutic potential of polymer-drug conjugates in joint inflammation, we synthesized polymer conjugates based on N-(2-hydroxypropyl) methacrylamide) copolymers labeled with a near-infrared fluorescent dye and covalently linked to the anti-inflammatory drug dexamethasone (DEX). The drug was bound to the polymer via a spacer enabling pH-sensitive drug release in conditions mimicking the environment inside inflammation-related cells. An in vivo murine model of adjuvant-induced arthritis was used to confirm the accumulation of polymer conjugates in arthritic joints, which occurred rapidly after conjugate application and remained until the end of the experiment. Several tested dosage schemes of polymer DEX-OPB conjugate showed superior anti-inflammatory efficacy. The highest therapeutic effect was obtained by repeated i.p. application of polymer conjugate (3 × 1 mg/kg of DEX eq.), which led to a reduction in the severity of inflammation in the ankle by more than 90%, compared to 40% in mice treated with free DEX.